Plasmapheresis in the Management of Acute Pancreatitis due to Severe Hypertriglyceridemia—Reporting New Cases - Andreia Campos; Josefina Santos; Cristina Freitas; Ana Castro; Sofia Santos; JP Pimentel; António Cabrita (Journal of Renal and Hepatic Disorders)
Acute pancreatitis is a potentially life-threatening disease. If the diagnosis and the treatment are not prompt, it can rapidly evolve to a medical emergency. Severe hypertriglyceridemia, defined as above 1000 mg/dl, is the third most common cause of acute pancreatitis. Conventional management includes fat dietary restriction and pharmacological treatment; however, these measures take time to be effective. Plasmapheresis seems to be an alternative and safe adjunctive therapy because it allows the rapid reduction of the trigger agent in circulation. Its use, especially in severe cases, has been increasingly reported. The authors report three cases of severe hypertriglyceridemia-induced pancreatitis in which early plasmapheresis was successfully used with other supportive clinical management.